Improving governance for anticipation, warning, action and financing climate disasters in Zambia - Acuda Opeto, Aaron; Osei-Amponsah, Charity; Amarnath, Giriraj (CGIAR System Organization, 2022)
This case study in Zambia examines existing Early Warning, Early Action and Financing (EWEAF) initiatives in response to floods. It looks at the institutional gaps, arrangements, innovations and challenges that may affect progress and speed of actions. It employs the concept of anticipatory governance and polycentric governance arrangements to identify the appropriate institutional conditions to support Governance 4 Resilience.